Body mass index, subjective body shape, and suicidal ideation among community-dwelling Korean adults - Chae Eun Yong; Young Bum Kim; Jiyoung Lyu (BMC, 2021)
Abstract Background Previous studies have not investigated in depth the combination of objective body weight and subjective body shape and its association with suicidal ideation among different age groups. Therefore, this study aimed to examine the abovementioned association among Korean adults, stratified by developmental stages. Methods We used nationally representative data from the 2017 Korean Community Health Survey, and included 222,037 participants aged 19 years or older in our study. Suicidal ideation was considered as the dependent variable (1 = yes, 0 = no). Along with body mass index (BMI) and subjective body shape measures, seven categories were created (1 = underweight-skinny, 2 = underweight-normal/fat, 3 = healthy weight-skinny, 4 = healthy weight-normal, 5 = healthy weight-fat, 6 = overweight-skinny/normal, 7 = overweight-fat). Multivariate logistic regression was conducted for each age group. Results Adjusted for covariates, young adults who were overweight-fat (OR = 1.18, p < .01), middle-aged adults who were underweight-skinny (OR = 1.32, p < .05), and older adults who were healthy weight-fat (OR = 1.19, p < .05) were more likely to have suicidal ideation than their healthy weight-normal counterparts. Conclusions The results suggest that the association between the combination of objective body weight and subjective body shape and suicidal ideation differs according to the developmental stage. Therefore, this difference should be considered when developing suicide prevention interventions based on the developmental stages.